Understanding Authenticity in YouTube Playful Talk: A Translingual Practice Approach - Obay Jambari; Setiono Sugiharto; Ferdinan Okki Kurniawan (Journal of General Education and Humanities, 2026)
This study addresses the limited research on how translanguaging operates within playful talk in audiovisual digital environments, particularly in relation to identity construction and authenticity negotiation. While previous studies have examined translanguaging in educational or written digital contexts, little attention has been given to its role in informal, multimodal interactions on platforms such as YouTube. This study aims to analyze how multilingual speakers employ translanguaging practices to construct social identities and negotiate authenticity in playful talk. This research adopts an interpretive qualitative approach using a case study design. The data were collected from one episode of the Playful Talk YouTube channel, focusing on a single participant (GS1). Data sources include video recordings and a semi-structured interview, which were analyzed using thematic and discourse-oriented analysis. The findings reveal that translanguaging functions as a structured communicative strategy rather than a random language alternation. English is predominantly used for affective expression and stance-taking, while Indonesian provides contextual elaboration and narrative grounding. These language choices enable the participant to construct hybrid identities that integrate local and transnational orientations. Furthermore, multimodal resources such as gestures and facial expressions are systematically aligned with linguistic shifts, reinforcing meaning-making and authenticity in interaction. This study contributes to digital sociolinguistics by demonstrating that translanguaging is not only linguistic but also multimodal and interactional. It offers a more integrated framework for understanding multilingual communication in digital environments and highlights the role of playful talk as a site of identity negotiation.